THE INFLUENCE OF THE LIFE CYCLE ON THE EFFICIENCY OF THE COMPANY'S INVESTMENT IN THE FOOD AND BEVERAGE SECTOR IN INDONESIA - Nabila Maharani; Raihan Fadhillah Aqshal; Elga Adestria; Farah Margaretha Leon (The Management Journal of Binaniaga, 2022)
This research examines the role of the Company Life Cycle stage in determining investment efficiency of 36 food and beverage companies listed on the Indonesia Stock Exchange for 4 years (2016-2019). And using multiple linear regression analysis method. The independent variable in this research is the Company Life Cycle, while the dependent variable is the company's investment efficiency. There are 3 control variables in this research, namely leverage, firm size, and cash flow. The results of this research indicate that the Company Life Cycle (Intro, Growth, Mature, and Decline) specifically Intro and Decline have no significant effect on Investment Efficiency 1, while Growth and Mature have a negative or significant effect on Investment efficiency 1. The results of this research can be useful for managers, policy makers, and investors. For Managers, this research encourages managers to adjust investment policies to the stages of the life cycle of each company. For policy makers, they will be able to optimize what policies should be implemented, while for investors, they will be wiser in making decisions in the efficiency of their investment portfolios.